The effect Syrian war on the trade and the role of sme development organization - Çörekçioğlu, Selim; Musayeva, Tahmina; Horuz, Deniz; Molnar, Mark (Studia Mundi – Economica, 2021)
In this paper, the effect of the Syrian war on the export of SMEs in Hatay province, located on the Syrian border, is investigated and the role of KOSGEB (SME Development Organization of Turkey) is discussed. For the analysis companies were selected from Hatay. The examined population consists of 1176 exporting enterprises which does export and the sample size was 107 units. Furthermore, an attempt is made to identify the relevant factors causing problems for the SME’s, namely if their country of origin, area of activity, export-orientation and export-intensity was a distinctive factor. It was found that export volume and KOSGEB’s subsidies was a significant factor in explaining business disruption, but other factors turned out to be irrelevant. This lead to the conclusion that the role and activity of KOSGEB (e.g. detailed company analyses, foreign market analyses, regional research and KOSGEB support) should be expanded to more companies.
Keywords: SME; Support; International; Trade